2014
DOI: 10.1680/gein.14.00019
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of geosynthetic reinforcement in widening of embankments subjected to foundation differential settlement

Abstract: In the present study, physical model tests were conducted to investigate the effect of the geogrid reinforcement on the reduction of the differential settlement in widening of a highway embankment. A water bag filled with water and placed beneath an embankment was used to simulate the soft foundation of the widened portion of the embankment in the physical model test. Water from the water bag was drained to simulate the development of differential settlements between the existing and widened foundations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…is section compares the results of the analytical calculations by this study and a rubber water bag trapdoor test conducted by Miao et al [35]. Di erent from the Villard and Briançon's [22] test, Miao et al [35] adopted a gradeddrainage subsidence manner to evaluate the reinforcing mechanism of the geosynthetic. e advantage is that the changes of displacement and stress of embankment and the response of reinforcing behavior can be recorded stepwise.…”
Section: According To the Initial And Boundary Conditionsmentioning
confidence: 93%
See 1 more Smart Citation
“…is section compares the results of the analytical calculations by this study and a rubber water bag trapdoor test conducted by Miao et al [35]. Di erent from the Villard and Briançon's [22] test, Miao et al [35] adopted a gradeddrainage subsidence manner to evaluate the reinforcing mechanism of the geosynthetic. e advantage is that the changes of displacement and stress of embankment and the response of reinforcing behavior can be recorded stepwise.…”
Section: According To the Initial And Boundary Conditionsmentioning
confidence: 93%
“…e rubber water bag trapdoor test conducted by Miao et al[35]. Comparison of load on the geosynthetic layer due to local subsidence.…”
mentioning
confidence: 99%
“…They showed that the geogrid reduces the differential settlement and horizontal displacement of new embankment combined with the sensitivity analysis by numerical simulation. A Laboratory physical model test of embankment conducted by Miao et al (2014) settlement by 20−30 mm, which indicates that the geogrid effectively reduces the differential settlement. Zhao et al (2019) investigated that the total settlement of embankment surface and lateral displacement after embankment construction are significantly reduced when prestressed tubular concrete (PTC) piles and geogrids were used to reinforce embankment.…”
Section: Research Progress Of Embankment Separated Widening and Isolating Wallmentioning
confidence: 98%
“…Aslam (2009a, 2009b) varied the stiffness of the subsoil by using two grades of EPS in their centrifuge tests. Chen et al (2008b) and Miao et al (2014) modelled the consolidation of the subsoil in their tests by gradually draining water out from water bags. Only a few (such as Zaeske 2001;Heitz 2006;Le Hello 2007, Chen et al 2008b, and van Eekelen et al 2012) included geosynthetic reinforcement.…”
Section: Introductionmentioning
confidence: 99%